A Light, investimento estrangeiro no Brasil: uma luz sobre o ciclo privado-público-privado em 80 anos pela análise de taxa de retorno - Jourdan, Marcelo Mollica (2006)
The Brazilian Traction, Light and Power Company, known to the public simply as Light, was formed by Canadian entrepreneurs in 1899. For the following 80 years, Light dominated the public services sector (tramways, electricity, telephones, gas) in the most developed areas of Brazil, the cities of Rio de Janeiro and São Paulo. Since its foundation, the company survived through various political times, until its takeover by the Brazilian government in 1979. During these eighty years, Brazilian infrastructure, born private, was gradually made public. In the 90s, the sector would be privatized, thus returning to its original state. The cycle, private-public-private, as seen in developed economies, was also experienced by Brazil. The Light, the major symbol of foreign capital in Brazil, was initially welcome given its identification with industrialization and modern times. The 20s, however, brought the debate over the role of foreign capital in Brazilian development, vis-à-vis the choice of the State as the leading player. A great deal of criticism was the norm in the case of Light, in particular regarding its profitability level, considered at the time to be obscure, possibly above the norm. Another point of debate refers to the lack of appropriate tariff corrections and to which extent this was a cause for recurrent supply crisis in the country´s infrastructure sector. Through primary research, this thesis analyzes Light´s history from a Rate-of-Return perspective. After constructing a (previously unavailable) data series for Light´s 80- years financial history in Brazil, it was possible to calculate its shareholders returns, for different periods and for its whole presence in Brazil. By comparing its returns against benchmarks, we were able to show that: i) contrary to the popular belief at the time, the rate-of-return obtained by the major foreign player in Brazil´s XXth century infrastructure, was actually well below minimum acceptable levels, and ii) the lack o proper tariff adjustments, for many decades, was in fact a key factor explaining the underdevelopment of Brazilian infrastructure sector.